Management of the Motor Disorders of Children with Cerebral Palsy / Second Edition - Damiano Diane; Mayston Margaret; Scrutton David (Cambridge University Press, 2004)
Foreword, Introduction, The Spectrum of Disorders Known as Cerebral Palsy, Families and Service Providers: Forging Effective Connections and Why it Matters, Goal Setting and the Measurement of Change, A Physiotherapy Perspective on Assessment and Outcome Measurement of Children with Cerebral Palsy, Neural Plasticity and Learning: The Potential for Change, The Assessment and Management of Hypertonus in Celebral Palsy: A Physiological Atlas, Mechanisms of Deformity, The Management of Deformity, Physiotherapy Management in Cerebral Palsy: An Update on Treatment Approaches, Physiotherapy Management in Celebral Palsy: Moving Beyond Philosophies, Cerebral Palsy in Adult Life, Therapeutic Possibilities: Research Overview and Commentary, Index.